A Review on Material Extrusion Additive Manufacturing of Metal and How It Compares with Metal Injection Moulding - Chanun Suwanpreecha; Anchalee Manonukul (Metals, 2022)
Material extrusion additive manufacturing of metal (metal MEX), which is one of the 3D printing processes, has gained more interests because of its simplicity and economics. Metal MEX process is similar to the conventional metal injection moulding (MIM) process, consisting of feedstock preparation of metal powder and polymer binders, layer-by-layer 3D printing (metal MEX) or injection (MIM) to create green parts, debinding to remove the binders and sintering to create the consolidated metallic parts. Due to the recent rapid development of metal MEX, it is important to review current research work on this topic to further understand the critical process parameters and the related physical and mechanical properties of metal MEX parts relevant to further studies and real applications. In this review, the available literature is systematically summarised and concluded in terms of feedstock, printing, debinding and sintering. The processing-related physical and mechanical properties, i.e., solid loading vs. dimensional shrinkage maps, sintering temperature vs. relative sintered density maps, stress vs. elongation maps for the three main alloys (316L stainless steel, 17-4PH stainless steel and Ti-6Al-4V), are also discussed and compared with well-established MIM properties and MIM international standards to assess the current stage of metal MEX development.